Pendampingan Sertifikasi Halal: Upaya Peningkatan Legalitas Produk Kelompok Usaha Perhutanan Sosial (KUPS) Desa Batu Raja Rejang, Kecamatan Hulu Palik, Kabupaten Bengkulu Utara - Anjelia Giovani; Khairiah Elwardah; Khozin Zaki (Universitas Muhammadiyah Surabaya, 2026)
This community service activity aims to assist the Social Forestry Business Group (KUPS) of Batu Raja Rejang Village, Hulu Palik District, North Bengkulu Regency in completing the halal certification process for Sako Lemo Nakai Coffee products, which had been delayed. The assistance was carried out through stages of survey and problem identification, education on halal certification, and collaborative continuation of the certification administration with the Halal Laboratory of UIN Fatmawati Sukarno (FAS) Bengkulu. The assistance process included restoring the Halal Information System (SIHALAL) account, checking the completeness of documents, and verifying the production process to ensure that the products are safe for consumption and meet halal requirements. The results of the activity show that structured and collaborative assistance can increase business actors' understanding of the importance of halal certification and successfully encourage the issuance of halal certificates by the Halal Product Guarantee Agency (BPJPH). This activity is expected to become a model for halal certification assistance for community-based micro businesses.